microRNAs, the Link Between Dengue Virus and the Host Genome - Su, Yinghua; Lin, Ting; Liu, Chun; Cheng, Cui; Han, Xiao; Jiang, Xiwen (Frontiers in Microbiology, 2021)
Dengue virus is a small envelope virus of Flaviviridae that is mainly transmitted by Aedes aegypti and Aedes albopictus. It can cause dengue fever with mild clinical symptoms or even life-threatening dengue hemorrhagic fever and dengue shock syndrome. At present, there are no specific drugs or mature vaccine products to treat dengue virus. MicroRNAs (miRNAs) are a class of important non-coding small molecular RNAs that regulate gene expression at the post-transcriptional level. It is involved in and regulates a series of important life processes, such as growth and development, cell differentiation, cell apoptosis, anti-virus and anti-tumor. miRNAs also play important roles in interactions between host and viral genome transcriptomes. Host miRNAs can directly target the genome of the virus or regulate host factors to promote or inhibit virus replication. Understanding the expression and function of miRNAs during infection with dengue virus and the related signal molecules of the miRNA-mediated regulatory network will provide new insights for the development of miRNA-based therapies.